2022
DOI: 10.3390/ijms23169291
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Bioactivity and Antibacterial Effects of a Silver-Containing Mesoporous Bioactive Glass Film on the Surface of Titanium Implants

Abstract: Peri-implantitis is defined as a bacterial infection-induced inflammation and suppuration of soft and hard tissues surrounding a dental implant. If bacteria further invade the alveolar bone, they can easily cause bone loss and even lead to the early failure of a dental implant surgery. In the present study, an 80SiO2–15CaO–5P2O5 mesoporous bioactive glass film system containing 1, 5, and 10 mol% of silver was prepared on titanium implant discs (MBG–Ag–coated Ti) using sol-gel and spin coating methods. The wett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
16
0
Order By: Relevance
“…Wang et al found that the MBG – Ag coating can convert the hydrophobicity of the titanium implant surface into hydrophilicity, and this mesoporous structure can also prolong the antibacterial time by controlling the release of Ag. May help prevent and treat early implant failure and peri-implantitis [ 218 ]. These results suggest that nanosilver coating is a promising material with antibacterial properties for implant abutments and prostheses to prevent peri-implantitis.…”
Section: Prosthodonticsmentioning
confidence: 99%
“…Wang et al found that the MBG – Ag coating can convert the hydrophobicity of the titanium implant surface into hydrophilicity, and this mesoporous structure can also prolong the antibacterial time by controlling the release of Ag. May help prevent and treat early implant failure and peri-implantitis [ 218 ]. These results suggest that nanosilver coating is a promising material with antibacterial properties for implant abutments and prostheses to prevent peri-implantitis.…”
Section: Prosthodonticsmentioning
confidence: 99%
“…To improve their performance, researchers have chosen to functionalize them further. Some studies have demonstrated that being loaded with antimicrobial peptides, antibiotics, bactericidal agents, or some metal ions can enhance their antibacterial properties [ 119 , 157 , 158 ]. Researchers previously grafted an antimicrobial peptide, Magainin I (Mag), to a titanium oxide surface [ 159 ].…”
Section: Anti-adhesion Strategies For Titanium Implantsmentioning
confidence: 99%
“…The success rate of Ti dental implant surgery can reach over 90%, but there are still about 10% failures . The key that determines the success of Ti implants is the effective osseointegration. In addition, improving the antibacterial properties of the implant and suppressing peri-implant inflammation are also important factors for the success of the surgery. Osteogenesis requires osteoblasts to adhere and grow on the surface of the implant. And the occurrence of inflammation is mostly related to bacterial adsorption and biofilm formation on the surface of implants. All of the above processes are closely related to the surface conditions of Ti implants. However, during the Ti implant manufacturing process, if the overall material is changed to achieve good surface conditions, the overall performance of the implant may be seriously affected.…”
Section: Introductionmentioning
confidence: 99%